Audio-describing visual filmic allusions. (3rd April 2017) - Lievois, Katrien; Remael, Aline
ABSTRACT: Filmic allusions, and especially different types of visual allusions, have become a staple of many film genres today. However, a systematic methodology for studying such allusions in film appears not to have been developed. The present study makes use of terminology and concepts from literary studies to analyse how specific references or markers in one film refer to marked items in another, older film, creating meaningful but often indirect links between the two productions. Using the audio-described version of a French parody film that abounds with allusions in different forms and combinations, Astérix et Obélix: Mission Cléopâtre, the study goes on to investigate how the audio-described version, which makes audiovisual products accessible for blind and visually impaired audiences by verbalizing the productions' visual narration, tackles these allusions and their indirect referencing system.